The potential of human regulatory T cells generated ex vivo as a treatment for lupus and other chronic inflammatory diseases - Horwitz, David A (BioMed Central, 2002)
Regulatory T cells prevent autoimmunity by suppressing the reactivity of potentially aggressive self-reactive T cells. Contact-dependent CD4(+) CD25(+) 'professional' suppressor cells and other cytokine-producing CD4(+) and CD8(+) T-cell subsets mediate this protective function. Evidence will be reviewed that T cells primed with transforming growth factor (TGF)-β expand rapidly following restimulation. Certain CD4(+) T cells become contact-dependent suppressor cells and other CD4(+) and CD8(+) cells become cytokine-producing regulatory cells. This effect is dependent upon a sufficient amount of IL-2 in the microenvironment to overcome the suppressive effects of TGF-β. The adoptive transfer of these suppressor cells generated ex vivo can protect mice from developing chronic graft-versus-host disease with a lupus-like syndrome and alter the course of established disease. These data suggest that autologous T cells primed and expanded with TGF-β have the potential to be used as a therapy for patients with systemic lupus erythematosus and other chronic inflammatory diseases. This novel adoptive immunotherapy also has the potential to prevent the rejection of allogeneic transplants.